DI BAWAH BAYANG-BAYANG MEDIA : Kodifikasi, Divergensi, dan Kooptasi Agama di Era Internet - Irwan Abdullah, Irwan Abdullah (Fakultas Ilmu Budaya Universitas Diponegoro, 2017)
Conventionally the construction of religious knowledge is carried out by the authority / person who has a scientific background and / or skills in the field of religion or the person who gets the legitimacy as a religious teacher, among others called ustadz, kiyai / or tengku. Religious knowledge is top-down because the production of knowledge and the truth of religion is determined by the religious elite so that the public becomes the object of religious. The new media era has changed the tendency of religious education by opening public participation in the production of religious knowledge. Religion becomes the object of daily conversation with diverse and contestative meanings, no longer absolute and elitist. The shift of the center of religious knowledge to the public has brought fundamental implications on the development of religion itself, with the occurrence of aqidah siltation, religious divergence / and co-optation of religion. The center of power shifts from the religious elite to the media that is present within the framework of political economic interests.